Board Monitoring, Audit Committee Effectiveness and Financial Reporting Quality - SHAN, YIBING (2017)
This study investigates the impact of The UK Corporate Governance Code (2016) on the quality of financial reporting. A number of prior studies have examined the role of the governance mechanisms in monitoring financial reporting quality, with mixed results. This paper extends prior research by combining two streams of research on financial reporting quality, i.e., the monitoring effectiveness of board of directors and audit committees. It is hypothesised that the quality of financial reporting is significantly related to the strength of corporate governance mechanisms, including the composition of board of directors, the personal attributes of outside directors and the characteristics of audit committees. The level of earnings management as a proxy for financial reporting quality is measured by absolute discretionary accruals based on Modified Jones model (1995). By investigating FTSE 100 companies listed on the London Stock Exchange over the period 2014 to 2016, this study demonstrates that the duality of the CEO and chairman has a negative association with financial reporting quality whereas audit committee independence is positively related to financial reporting quality. These relations are statistically significant and robust to alternative specifications. Supplemental tests, by using signed discretionary accruals or change in discretionary accruals as a measure of earnings management, indicate the similar results. In addition, the supplemental tests also show that frequent board meetings have a positive impact on financial reporting quality, while the experienced outside directors have a negative impact on financial reporting quality. Additionally, results in sensitivity tests indicate that an fully independent audit committee is positively related to financial reporting quality. The results suggest that board of directors is an important factor in monitoring the quality of UK firms’ financial reporting. The results also indicate that audit committees, concerned with both income-increasing and income-decreasing earnings management, are effective in the financial reporting process by reducing the magnitude of earnings management. The results of this study provide useful guidelines to regulators, companies and academics.